2021
DOI: 10.1021/acsomega.1c02487
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diel Cycling Temperature, Relative Humidity, and Synthetic Route on the Surface Morphology and Hydrolysis of α-U3O8

Abstract: The speciation and morphological changes of α-U 3 O 8 following aging under diel cycling temperature and relative humidity (RH) have been examined. This work advances the knowledge of U-oxide hydration as a result of synthetic route and environmental conditions, ultimately giving novel insight into nuclear material provenance. α-U 3 O 8 was synthesized via the washed uranyl peroxide (UO 4 ) and ammonium uranyl carbonate (AUC) synthetic routes to produce unaged starting materials with different morphologies. α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…U 3 O 8 has different types of oxygen bonded to uranium, yielding different bond lengths. At room temperature (orthorhombic structure), two uranium atoms [labeled U(1) and U(2)] are surrounded by six oxygen atoms at distances between 2.07 and 2.23 Å, with the seventh oxygen atom bonded to U(1) and U(2) at distances of 2.44 and 2.71 Å, respectively. Loopstra established that the room-temperature orthorhombic and high-temperature hexagonal structures are similar, except that the hexagonal structure has one uranium site, whereas the orthorhombic structure has two. However, the surrounding oxygens are approximately equivalent for both lattice types …”
Section: Introductionmentioning
confidence: 99%
“…U 3 O 8 has different types of oxygen bonded to uranium, yielding different bond lengths. At room temperature (orthorhombic structure), two uranium atoms [labeled U(1) and U(2)] are surrounded by six oxygen atoms at distances between 2.07 and 2.23 Å, with the seventh oxygen atom bonded to U(1) and U(2) at distances of 2.44 and 2.71 Å, respectively. Loopstra established that the room-temperature orthorhombic and high-temperature hexagonal structures are similar, except that the hexagonal structure has one uranium site, whereas the orthorhombic structure has two. However, the surrounding oxygens are approximately equivalent for both lattice types …”
Section: Introductionmentioning
confidence: 99%
“…U 3 O 8 microplates have already been reported and were formed from the thermal decomposition of uranyl ammonium carbonate. U 3 O 8 mp reported here could be used as precursors to prepare several other uranium oxide materials (UO 2 , UO 3 ) with a rectangular geometry, enabling investigations on the effects of morphology (i.e., mp vs ms) of uranium oxides on several physicochemical properties (i.e., catalysis).…”
Section: Resultsmentioning
confidence: 99%
“…Controlling particle morphology is of great importance to many industries including semiconductors, nanomaterials, and steel fabrication. Levlev et al showed that a mechanistic understanding of nucleation and growth mechanisms can lead to improved modeling of material properties and future material discovery . In the nuclear industry, particle morphology can impact the environmental transport of uranium, nuclear fuel performance in reactors, long-term storage of spent nuclear fuel, and support nuclear forensics and nuclear safeguards in identifying the processing history of nuclear materials. ,, Prior studies have identified many variables including pH, temperature, reaction time, and calcination temperature that impact the final particle morphology. Advancements in particle segmentation and machine learning enable quantification of even subtle morphology changes. , The challenge, however, has been in understanding the fundamental principles that result in unique particle morphologies based on the chemical and physical processing conditions. In situ liquid phase transmission electron microscopy can help reveal the underlying mechanisms of particle formation, particularly when the impacts of radiolysis can be mitigated. , In the case of studtite, electron beam radiolysis of uranyl solutions enables the controlled in situ precipitation of particles under different reaction conditions.…”
Section: Introductionmentioning
confidence: 99%